2013
DOI: 10.1038/ijo.2013.233
|View full text |Cite
|
Sign up to set email alerts
|

Comprehending emotional eating in obese youngsters: the role of parental rejection and emotion regulation

Abstract: The findings highlight the importance of assessing the emotional bond between mother and child and the emotion regulation of the youngster in the treatment of pediatric obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
68
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(79 citation statements)
references
References 51 publications
9
68
2
Order By: Relevance
“…While the current study examined self-reported LOC eating behavior and objective energy intake, we did not specifically assess eating in response to acute negative affect. Indeed, emotional eating has been linked to emotion dysregulation (Vandewalle et al, 2014). However, given that emotional eating has not been shown to predict excess weight or fat gain, we opted to study self-reported LOC eating, a construct that has been consistently associated with adverse outcomes (Tanofsky-Kraff et al, 2006; Tanofsky-Kraff et al, 2012; Tanofsky-Kraff, Yanovski, et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the current study examined self-reported LOC eating behavior and objective energy intake, we did not specifically assess eating in response to acute negative affect. Indeed, emotional eating has been linked to emotion dysregulation (Vandewalle et al, 2014). However, given that emotional eating has not been shown to predict excess weight or fat gain, we opted to study self-reported LOC eating, a construct that has been consistently associated with adverse outcomes (Tanofsky-Kraff et al, 2006; Tanofsky-Kraff et al, 2012; Tanofsky-Kraff, Yanovski, et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…General linear models (GLM) were used to examine differences in parent-reported emotion dysregulation by LOC status. Covariates included age (Zimmermann & Iwanski, 2014), puberty (Crockett, Carlo, Wolff, & Hope, 2013), race (coded as non-Hispanic White or Other) (Chapman & Mullis, 2000), sex (Zimmermann & Iwanski, 2014), and fat mass (%, arcsine transformed) (Vandewalle, Moens, & Braet, 2014). GLM analyses were also used to examine the main and interaction effects of self-reported LOC status and parent-reported emotion dysregulation (centered based on the grand mean to reduce multicollinearity concerns) (Cohen, Cohen, West, & Aiken, 2003) on BMI z and fat mass.…”
Section: Methodsmentioning
confidence: 99%
“…Consequently, emotional eating is the result of self-inability to regulate emotions, and this maladaptive strategy might underlie the relationship between emotional dysregulation and obesity by modifying dietary intake (50,51,65) . Studies in children and adolescents have revealed an association between maladaptive ER strategies and emotional eating (83,(86)(87)(88) . However, different maladaptive strategies of ER have been assessed in these studies and this may lead to bias in the results.…”
Section: Physiological Mechanisms Leading To Obesitymentioning
confidence: 99%
“…Finally, it is strongly supported that certain parenting styles, such as the authority and permissive parenting style, increase the risk of overweight (59,114) , especially those children who fail to delay gratification or have poor self-regulation (115) . Indeed, it has been suggested that ER mediates the relationship of parental attachment with emotional eating or unhealthy food consumption and sedentary activities in children (87,112) .…”
Section: Nutrition Research Reviewsmentioning
confidence: 99%
“…Some studies indicate that obesity is related to disturbed general ways to regulate and process emotions, which in turn may indicate emotional eating, the tendency to eat when experiencing negative affect [8][9][10][11]. The concept of emotional eating derives originally from Bruch's psychosomatic theory [12,13] in which eating is considered to be a response to distress, as consequence of an inability to distinguish hunger from other aversive internal states, probably because of early learning experiences.…”
Section: Introductionmentioning
confidence: 99%